CONSTRAINTS PERCEIVED BY THE DAIRY FARMERS IN ADAPTING TO CHANGING CLIMATE IN WESTERN DRY REGION OF INDIA - Sankhala, Gopal —; KANT, KAMALA; PRASAD, KAMTA (Indian Journal of Dairy Science, 2015)
Dairy farming is vulnerable to climate variability through increased temperature, variation in sunshine and changes in rainfall pattern. These factors adversely affect feed & water availability, animal health, breeds and in turn milk production. Warmer and drier conditions increase the likelihood of heat stress in cattle. Heat stress adversely affects reproductive performance in dairy animals. In this direction, the research was designed with the objective of constraints perceived by the dairy farmers in adapting to changing climate in Western dry Region of India. Data for the study were collected through proportionate random sampling method from a total of 240 respondents using both qualitative and quantitative techniques. The data were analysed using frequency and percentage. The findings of present study show that the major constraints were repeat breeding, lack of knowledge about climate impacts, high cost of concentrate, absence of government policy on climate problems, lack of pasture, non-availability of weather information. The most important suggestions received from the respondents to overcome these constraints, were organization of awareness campaign about climatic problems, growing of improved and drought resistant grasses on pasture land, provision of good quality bull and provision of animal health services at nominal rate